Gratitude, Optimism, Religiosity, and Subjective Well-Being among Asthma Patients in Yogyakarta, Indonesia - Sulistyarini, Raden Rara Indahria; Novita, Diah Ayu; Pambudiarti, Dayu Arya; Pratiwi, Eka Ayu; Andriansyah, Yuli (International Journal of Innovative Research and Scientific Studies, 2022)
This research aimed to analyze the correlation between three variables (gratitude, optimism, and religiosity) and subjective well-being among asthma patients. The subjects of this research were 160 Muslim asthma patients aged 18-39 years-old in Yogyakarta, Indonesia. Data were collected using researcher-administered questionnaires consisting of five scales. Subjective well-being was measured using two scales: Positive Affect and Negative Affect Schedule (PANAS) scale and Satisfaction with Life Scale (SWLS). Gratitude was measured using the Psychological Measure of Islamic Gratitude (PMIG) scale. Optimism was measured using the Life Orientation Test-Revised (LOT-R) concept. Religiosity was measured using five dimensions: belief, religious practices, religious experiences, religious knowledge, and practicing and consequence. The result showed a positive correlation between three variables (gratitude, optimism, and religiosity) and subjective well-being among asthma patients. Furthermore, the results also showed that there was no significant difference of subjective well-being between male and female subjects, between adolescent and adult subjects, and between groups of subjects based on duration of being diagnosed with asthma.